Sosialisasi Penggunaan Gadget terhadap Perkembangan Psikologi pada Anak Sekolah Dasar - Regina Sipayung; Patri Janson Silaban; Hartati Anna Siregar; Masli Tamba; Anastasya Simamora; Margaretha Ayu Lumban Gaol; Debora Panjaitan (Jurnal Kabar Masyarakat, 2024)
Studies on the influence of gadgets on children's psychological development show that there is a significant impact. A study at SD NEGERI 104215 SUDIREJO found that the use of gadgets by class IV students had a significant influence on children's psychological development. The negative impact of gadget use by other studies shows that the use of gadgets can have an impact. on emotional growth, attention disorders, and emotional disorders in children. Apart from the negative impacts, there are also positive impacts, namely, children can easily find information about learning and can facilitate communication with friends.